Institutional Culture & Academic Entrepreneurship Averting a Crisis and Salvaging the Last Bastion of Competitiveness - Srinivas, Vijay (Journal of Engineering Education Transformations, 2016)
Federal research funding for universities (chiefly, NSF, NIH, DOD, DOE) stands at a staggering 30 billion dollars or so, and there is an increasing level of questioning and scrutiny as to the return on investment for such dollars, interms of societal economic impact both within the funding agencies and by our elected representatives. Figuring out ways to foster and sustain academic entrepreneurship (industry engagement; licensing of IP; launching start-ups) may be the way to take advantage of industry funding for research, while also ensuring that research of anapplied nature (particularly in engineering programs) can directly solve industry problems and thus support the creation of jobs. Thirty years after the Bayh-Dole Act-meant to encourage academic entrepreneurship, we find ourselves where university-industry interaction is still not pervasive. The proposed research is predicated on the notion that organizational culture (policies, processes, beliefs, and attitudes) have a significant influence on academic entrepreneurship. An understanding of the institutional culture and how it correlates to entrepreneurial activities of faculty can thus be instructive and helpful. The proposed study aims to identify and understand this. The proposed research is guided by initial insights obtained from a small set of (6 faculty) open-ended interviews that were conducted as pilot data collection. This was complemented by an autoethnographic examination of university culture, carried out over the course of a semester to examine university-industry interactions. Data collection via a designed survey instrument is being proposed as the means for obtaining the data for subsequent analysis and interpretation. Understanding the drivers (institutional culture) of academic entrepreneurship and the measures of an entrepreneurial culture can, in the long-run, play a pivotal part in universities embracing their 3rd mission-that of economic impact and industry development (the first 2 missions being teaching and research).